STEAM for sustainability: integrating statistics and science education in a rural context (Innovaciones Educativas, 2023)
In recent years, there has been a growing interest in responding to the social, environmental and economic crises of the contemporary world. To this end, Education for Sustainable Development (ESD) and STEAM (Science, Technology, Engineering, Art and Mathematics) Education have been promoted as strategies to face these problems. However, new approaches of an interdisciplinary nature have received little or no attention in rural contexts. From this perspective, our objective is to describe the systematization of a STEAM activity for sustainable development in a rural multigrade context, with students from 10 to 12 years old. For this purpose, a brief conceptual description of STEAM education, ESD and its presence in rural contexts is made. Subsequently, the process of designing an activity based on an integrated didactic unit (UDI), its implementation and some assessments of its impact on the school community are described. From the design and implementation of the ILU, which integrates the phases of a statistical research cycle with scientific research, it is concluded that: a) moving towards a sustainable society requires a comprehensive and equitable education that permeates all school contexts, including rural ones; b) the rural context offers a unique opportunity to develop contextual and interdisciplinary learning and, thus, promote sustainability competencies; and c) statistical research is an optimal resource to expand contributions involving STEAM education and ESD in rural contexts.
Keywords: Education for sustainable development; STEAM; Statistical Education; science education; rural context; primary education